2015
DOI: 10.1175/mwr-d-15-0059.1
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Implicit Version of the MPAS-Atmosphere Dynamical Core

Abstract: An important question for atmospheric modeling is the viability of semi-implicit time integration schemes on massively parallel computing architectures. Semi-implicit schemes can provide increased stability and accuracy. However, they require the solution of an elliptic problem at each time step, creating concerns about their parallel efficiency and scalability. Here, a semi-implicit (SI) version of the Model for Prediction Across Scales (MPAS) is developed and compared with the original model version, which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Since advective transport is about an order of magnitude slower than acoustic pressure oscillations, CFL h ≈ 10 and L ≈ 4 irrespective of the model resolution. As was demonstrated in [2,5], this "shallow" multigrid works well, and avoids expensive global communications. It also significantly simplifies the parallel decomposition, since it is only necessary to (horizontally) partition the coarsest grid, which still has a large number of cells and allows a relative fine-grained domain decomposition.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Since advective transport is about an order of magnitude slower than acoustic pressure oscillations, CFL h ≈ 10 and L ≈ 4 irrespective of the model resolution. As was demonstrated in [2,5], this "shallow" multigrid works well, and avoids expensive global communications. It also significantly simplifies the parallel decomposition, since it is only necessary to (horizontally) partition the coarsest grid, which still has a large number of cells and allows a relative fine-grained domain decomposition.…”
Section: Introductionmentioning
confidence: 74%
“…An exception is the recent implementation of the MPAS model. In [5] it is shown that a semiimplicit methods with a multigrid solver can be competitive with fully explicit time integrators. A conditional semi-coarsening multigrid for the ENDGame dynamical core [48] used by the Met Office is described in [49] and currently implemented in the Unified Model code.…”
Section: Parallel Multigrid and Atmospheric Modelsmentioning
confidence: 99%
“…For example, the choice of a loose linear solver tolerance improves efficiency but can prevent overall nonlinear convergence. Similar efforts to tease out the performance trade-offs with iterative schemes also recommend the fewest iterations to maintain stability and yet minimize cost (Sandbach et al, 2015). For the test cases analyzed presently, the optimal tolerance depends on the spatial grid and time step size.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that subcycling can present new errors and instabilities associated with time splitting in related applications (Estep et al, 2008). Other models use a form of semi-implicit methods (Å ström et al, 2012;Sandbach et al, 2015), which take advantage of scale separation to isolate and solve the relatively fast linear gravity waves efficiently. For high resolution configurations, semi-implicit schemes still require subcycling within subcomponents, and that can result in reduced solution accuracy, depending on the splitting strategy (Knoll et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While such an approach has been applied and proved effective in the context of grid‐based atmospheric models (e.g. Heikes et al ; Sandbach et al ), implementing it on current spectral models is not straightforward because the aforementioned non‐nested nature of Gaussian quadrature necessitates some form of accurate off‐grid interpolation (Jones, ; Ullrich et al ) from higher‐ to lower‐resolution grid (and vice versa). Appendix C gives further discussion.…”
Section: Introductionmentioning
confidence: 99%